Assistance For Institutional Strengthening of Urban Farming Groups Based on Urban Wetland Biodiversity - Sri Hidayah; Dimas Asto Aji An'Amta; fadly fadly; M Najeri Al Syahrin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Limited institutional capacity is the main obstacle for urban farming groups in Sungai Andai Village, North Banjarmasin. Unorganized organizational structures and unclear division of roles lead to weak coordination and decision-making. The purpose of this service activity is to strengthen the institutional capacity and management of the group through the arrangement of organizational structures, division of roles, and strengthening the network of external partnerships. The program was carried out for six months with participatory methods in the form of group discussions, focus group discussions (FGDs), workshops, training, and mentoring. The activity partner is the Puma III Wine Village Group which consists of 14 members. Evaluations are carried out periodically at the end of each month using observations, interviews, and online questionnaires. The results showed an increase in member participation from 70% to 92%, an increase in material understanding from 65% to 91%, and an increase in institutional capacity from 60% to 90%. In addition, the group succeeded in compiling a functional organizational structure, an annual work plan, and guidelines for biodiversity-based urban farming businesses. This activity proves that institutional strengthening accompanied by sustainable partnerships is able to strengthen the role of urban farming groups in realizing competitive and sustainable urban agriculture.